Health and literacy in first- and second-generation Moroccan Berber women in the Netherlands: Ill literacy? - Lhajoui Mina; Bekker Marrie HJ (BMC, 2004)
Abstract Aim The present study was aimed at investigating the role of literacy and generation in the self-reported general health status of Moroccan Berber speaking women in the Netherlands. Method Fifty women in our sample (N = 75) were first generation women, from which group 25 were literates and 25 illiterates. Another group of 25 literate women belonged to the second generation. The three groups were matched for demographic characteristics. Questionnaires were administered reflecting all concepts under study. We hypothesized that, within the first generation, illiterates compared with literates would report worse health. Our second hypothesis was that literates of the first generation compared with those of the second generation would have a similar health condition. Results After controlling for age, having a job, and having an employed partner, the first generation literates compared with the illiterates of the first generation indeed reported significantly better health. Additionally, we did not find any differences in health condition between both literate groups, even after controlling for age, number of children, and marital status. Health complaints that were most frequently reported by both groups, concerned pain in shoulders, back and head. Conclusions Our results underline the importance of offering immigrants optimal access to opportunities and facilities that can improve their literacy and reading ability.